Optimasi Rute Pengiriman Barang dengan Meminimumkan Biaya Transportasi Menggunakan Metode Saving Matrix di PT. Amanah Insanillahia - Rida arifi; Defri Ahmad (Journal of Mathematics UNP, 2019)
Abstract– The main problem in the distribution of stuff to consumers is the optimization of costs and shipping routes. PT. Amanah Insanillahia is a bottled mineral water company that distributes its products to every sub-district in Tanah Datar district. However, this company has not yet optimized its distribution cost. To do this optimization requires a transportation method to minimize costs and routes, namely the Saving Matrix method. The Saving Matrix method aims to determine the product distribution route to the marketing area by determining the distribution route that must be traversed and the number of vehicles based on the capacity of the vehicle in order to obtain the shortest route and minimum transportation costs.  The results of the transportation costs of distributing stuff at PT. Amanah Insanillahia by using this method can reduce costs by 35.11% with the optimum distribution route of stuff, namely the first route delivers of stuff carried out, namely Pariangan and Batipuh Districts. The second route is the Sungayang and Rambatan Districts. The third route is Limo Kaum and Lintau Districts. The fourth route is Salimpaung and Sungai Tarab District. Finally the fifth route is Tanjung Emas District. Keywords– Saving Matrix, distribution of stuff